2006
DOI: 10.1111/j.1479-8425.2006.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sleep architecture in practitioners of Sudarshan Kriya yoga and Vipassana meditation

Abstract: Yoga is an ancient Indian science and way of life that has been described in the traditional texts as a systematic method of achieving the highest possible functional harmony between body and mind. Yogic practices are claimed to enhance the quality of sleep. Electrophysiological correlates associated with the higher states of consciousness have been reported in long-term practitioners of transcendental meditation during deep sleep states. The present study was carried out to assess sleep architecture in Sudars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 33 publications
5
37
1
Order By: Relevance
“…Slow-wave sleep remained pathologically truncated between 5–8% following treatment. Two cross-sectional studies have reported increased slow-wave sleep in advanced meditators [58, 59], but we did not replicate this finding in the context of a longitudinal RCT of meditation-naïve ADM users. While there was no change in SWS or stage 1 in this sample, several other studies suggest that meditation may decrease sleep depth and increase wakefulness or cortical arousal [28, 6065].…”
Section: Discussioncontrasting
confidence: 68%
“…Slow-wave sleep remained pathologically truncated between 5–8% following treatment. Two cross-sectional studies have reported increased slow-wave sleep in advanced meditators [58, 59], but we did not replicate this finding in the context of a longitudinal RCT of meditation-naïve ADM users. While there was no change in SWS or stage 1 in this sample, several other studies suggest that meditation may decrease sleep depth and increase wakefulness or cortical arousal [28, 6065].…”
Section: Discussioncontrasting
confidence: 68%
“…The resultant calming effect on the stress response system could bring down the levels of anxiety and relieve depression as suggested by earlier reports on Sudarshan Kriya yoga and Vipassana meditation. [24] These postulates are supported by previous evidence that integrated yoga practice produces multi-dimensional, immediate benefits on physical and mental health by homeostatic regulation of hypothalamic-pituitary-adrenal axis and sympathetic nervous system. [25]…”
Section: Discussionmentioning
confidence: 72%
“…Studies by Sulekha et al (2006) and Ravindra et al (2010) demonstrated the differences in sleep architecture in practitioners of Vipassana meditation (mindfulness meditation). The sleep architecture of senior practitioners of Vipassana meditation was endowed with enhanced states of SWS and REM sleep compared to that of non-meditating control group.…”
Section: Meditation Brain Functions and Sleepmentioning
confidence: 99%